De Thooren in Maasniel (Bulletin KNOB, 1995)
In the written sources there is not much to be found on the history of De Thooren Castle. For that reason it is difficult to place De Thooren in its historical and social context. From an architectural point of view the building, with exterior measurements of 6.90 by 5.75 metres and a wall thickness of 0.90 m. at cellar level, is among the smaller towers in the region.Most residential towers have heavier walls. Very little is known about the oldest building phase, of which the walls - made of marlstone blocks - were found in the cellar. After the destruction of this building phase the residential tower was rebuilt. This second residential tower has been preserved remarkably intact until our present time.This tower consisted of a rectangular, tenable building made of brick, with four floors (including the cellar and the attic with roof construction), the uppermost of which was provided with an allure and crenelles (illustration 12). Originally all the rooms had wooden floors, later those of the cellar and ground floor were replaced by vaults.The first floor is probably the most representative part. This room is directly connected with outside by the wall stairs, so that the ground floor (which could be locked off by a door) need not be used for that purpose. In view of the very small windows it is not likely that the tower was used for permanent residence. Unlike common practice, the latrine is not on the residential level but on the level of the allure.No traces have been found of any original 14th- or 15th-century extensions. The indications referred to above suggest that the tower was probably not primarily intended for residential purposes, but is rather to be regarded as a status symbol and last resort. We may also take into account that the tower was used as (harvest) storage.